Multicultural Islamic Education Genealogy at Al-Hikam Student Islamic Boarding School of Malang - Abd. Syakur; Maskuri Bakri; H.M. Djunaidi Ghony (Budapest International Research and Critics University, 2021)
Multicultural education become discussion subject that is always interesting and sustainable, especially in Islamic boarding schools such as the Al-Hikam Student Islamic Boarding School which is admired by students. In this discourse, it is qualitative research with genealogical approach to multicultural based PESMA with methods of observation, interviews and documentation studies, there are many phenomenal things from the existence of the Student Islamic Boarding School. Starting from the genealogy of its establishment to its modern system and style, it still has the boarding school specialty. As has also been done at the time of the Prophet, the caliphate time to Indonesia in the past, in terms of its vision and mission to its main goal, it should be used as an example and model for multicultural education in this modern era. With that spirit, the Al-Hikam Student Islamic Boarding School has become pioneer in integrating Islamic boarding school religious knowledge with science in the university environment. In addition to the vision, mission and goals, the diverse students are the response of the founders to the advances of the times, so that the establishment of the Student Islamic Boarding School system until now remains solid and develops in the hope able to provide multidisciplinary, interdisciplinary and highly competitive human resources and upholding pluralism.